The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3168/jds.2020-18565
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for methane emission traits in Australian dairy cows

Abstract: Methane is a greenhouse gas of high interest to the dairy industry, with 57% of Australia's dairy emissions attributed to enteric methane. Enteric methane emissions also constitute a loss of approximately 6.5% of ingested energy. Genetic selection offers a unique mitigation strategy to decrease the methane emissions of dairy cattle, while simultaneously improving their energy efficiency. Breeding objectives should focus on improving the overall sustainability of dairy cattle by reducing methane emissions witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 33 publications
4
40
2
Order By: Relevance
“…This was expected, as the only difference was that RMet3 takes into account the 3 traits at the same time (MBW, DMI, and ECM) instead of 2 at a time (RMet1 and RMet2). Likewise, Richardson et al (2021) reported strong genetic (>0.71) and phenotypic (>0.87) correlations between 9 definitions of residual CH 4 involving DMI, ECM, and FeedSaved (amount of feed saved per year through assumed improvements in lifetime metabolic efficiency and reduced maintenance requirements) values in Australian Holstein cattle. Furthermore, Richardson et al (2021) reported genetic correlations between 0.52 to 0.97 between the different residual CH 4 traits and MeP, MeY, and MeI.…”
Section: Correlations Within Methane Traitsmentioning
confidence: 96%
See 4 more Smart Citations
“…This was expected, as the only difference was that RMet3 takes into account the 3 traits at the same time (MBW, DMI, and ECM) instead of 2 at a time (RMet1 and RMet2). Likewise, Richardson et al (2021) reported strong genetic (>0.71) and phenotypic (>0.87) correlations between 9 definitions of residual CH 4 involving DMI, ECM, and FeedSaved (amount of feed saved per year through assumed improvements in lifetime metabolic efficiency and reduced maintenance requirements) values in Australian Holstein cattle. Furthermore, Richardson et al (2021) reported genetic correlations between 0.52 to 0.97 between the different residual CH 4 traits and MeP, MeY, and MeI.…”
Section: Correlations Within Methane Traitsmentioning
confidence: 96%
“…Likewise, Richardson et al (2021) reported strong genetic (>0.71) and phenotypic (>0.87) correlations between 9 definitions of residual CH 4 involving DMI, ECM, and FeedSaved (amount of feed saved per year through assumed improvements in lifetime metabolic efficiency and reduced maintenance requirements) values in Australian Holstein cattle. Furthermore, Richardson et al (2021) reported genetic correlations between 0.52 to 0.97 between the different residual CH 4 traits and MeP, MeY, and MeI. In addition, Donoghue et al (2016) reported lower to moderate genetic correlations (0.32-0.63) and strong phenotypic correlations (0.60-0.76) between MeP and 4 residual CH 4 traits.…”
Section: Correlations Within Methane Traitsmentioning
confidence: 96%
See 3 more Smart Citations